Journalism and the social construction of reality: a contribution to the theoretical debate - Silveira, Patrícia (2014)
This article aims to reflect on the relationship between journalism and the production of knowledge, based on a set of provisions which, under the influence of phenomenology, allow to develop a "communication theory applied to journalistic media" (Correia, 2009:1). In this sense, we analyze the relevance of journalism for worlds apprehension, based on the unfolding of the concept of social construction of reality. This constructionist view allowed the neglet of an objectivist perspective, limiting the social effects of the media on issues of behavioral order, in favor of the recognition of the role of media communication for social cognition.